Hydraulic performance of geosynthetic clay liners to sulfuric acid solutions. Issue 1 (February 2015) - Liu, Y.; Bouazza, A.; Gates, W.P.; Rowe, R.K.
Abstract: The ability of geosynthetic clay liners (GCLs) to contain acidic mining leachates is examined. The results of saturated hydraulic conductivity ( k ) of two GCLs permeated with sulfuric acid solutions (H2 SO4 ) at 0.015 M, 0.125 M and 0.5 M concentrations are reported. Also, the saturated k values of consolidated (35 kPa) bentonite cakes made from sodium bentonite extracted from both GCLs were compared to a commonly used magnesium–sodium form bentonite. Chemical compatibility and effects of pre-hydration and effective stress were assessed as part of this study. Results indicated that an increased acid concentration (ionic strength) increased the k of all tested specimens. The ratio of the k 0.5 values for non-prehydrated specimens permeated with 0.5 M H2 SO4 to the k w values for specimens permeated with deionized (DI) water ( k 0.5 / k w ) ranged from 10 to 110. Pre-hydration (50–140% water content) and increased effective stress (35–200 kPa) improved the performance of GCLs (lower k ). Strong correlations were observed between k and liquid limit and swell index parameters independent of pre-hydration and effective stress in this study. However, care should still be taken when using these correlations to evaluate hydraulic performance because the intrinsic micro-structure properties of bentonite, such as porosity, should also be considered. This work showed that, for example, high SI of bentonite does not translate necessarily to a better hydraulic performance of GCLs.